Implementing Locally Tailored Strategies to Promote Redemption of Farmers' Market Nutrition Program Vouchers Among WIC Participants in Central Pennsylvania. Issue 1 (November 2022) - Calo, William A.; Marin, Evelyn; Aumiller, Betsy; Murray, Andrea; Baptiste, Claire; Bermudez, Madeline; Crawford, Laurie; DeLoatch, Vicki; Kraschnewski, Jennifer L.
The Pennsylvania Farmers' Market Nutrition Program (FMNP) provides vouchers to participants of the Special Supplemental Nutrition Program for Women, Infants, and Children (WIC) to purchase locally grown fruits, vegetables (F&V), and herbs every year from June to November. Voucher redemption is suboptimal among WIC participants in Lebanon County, a community with high numbers of low-income and Hispanic families. Supported by a Racial and Ethnic Approaches to Community Health (REACH) award, our community–academic coalition partnered with the local WIC provider to implement locally tailored strategies to promote redemption of FMNP vouchers. In 2019, we surveyed FMNP participants ( n = 100) to examine opportunities for improved voucher redemption. Increasing sites for voucher use (47%) and a larger variety of F&V (27%) were the most commonly selected improvements participants identified. Participants also supported improvements to increase awareness of available seasonal produce (14%), text/phone reminders to redeem vouchers (13%), and having recipes to cook meals with FMNP-approved F&V (12%). These findings led us to implement a weekly, Farm-to-WIC "grab bag" program in 2020/2021. We partnered with a local farmer to offer a variety of FMNP-approved produce in 3 and 6 grab bags at the local WIC provider. Each grab bag included healthy recipes using the included produce. In 2021, we launched a text/phone reminder intervention to encourage voucher redemption among FMNP participants (n = 57). Our work demonstrates the value of community–academic partnerships to identify and implement feasible strategies that are responsive to local needs as well as supporting existing programs providing greater access to affordable produce.